Acetylsalicylic Acid and Sodium Salicylate Inhibit LPS-lnduced NF-kB/c-Rel Nuclear Translocation, and Synthesis of Tissue Factor (TF) and Tumor Necrosis Factor alfa (TNF-a) in Human Monocytes - Osnes, L T N; Foss, K B; Joø, G B; Okkenhaug, C; Westvik, Å-B; Øvstebø, R; Kierulf, P (Thrombosis and Haemostasis, 1996)
We have investigated the effects of acetylsalicylic acid and sodium salicylate on the LPS-induced synthesis of the pro-coagulant protein tissue factor (TF) and the pro-inflammatory protein tumor necrosis fac-tor-a (TNF-a), as well as the prostaglandin PGE2 in human monocytes. Both drugs dose-dependently inhibited LPS-induced TF and TNF-a synthesis at the mRNA and the protein level, and reduced PGE2 production. As evidenced by electro mobility shift assay (EMSA) and the use of a NF-kB prototypic probe, these drugs probably exert their inhibitory effects by interference with the nuclear translocation of NF-KB/c-Rel proteins. These data may expand the understanding of the anti-thrombotic and anti-inflammatory effects of these drugs when activation of monocytes occurs.